THE GROWTH PERFORMANCE OF INDIA.S TELECOMMUNICATIONS SERVICES INDUSTRY, 1991-2006 CAN IT LEAD TO THE EMERGENCE OF A DOMESTIC MANUFACTURING HUB? - Sunil Mani (Centre for Development Studies-WP390, 2007)
India's economy is much more integrated with rest of the world now than it was in 1991. Several factors have facilitated this, some fiscal and some physical. One of the most important physical factors is the spectacular growth of telecommunications in India. An important facet of this revolution has been the phenomenal increase in the number oftelephones in the country although its spatial distribution still is a problem. A distinguishing aspect of this growth performance is that India now has five mobile phones for every one fixed telephone and the monthly additions to mobile subscribers are well over six million. Such a huge growth in telecom services have a number of spillover effects for rest of the economy and one of the more important effects is its potential to create a major manufacturing hub in the country for the manufacture oftelecom equipments and indeed for downstream industries such as semiconductor devices that are required for the manufacture of these equipments. The telecom industry in India is thus slowly emerging as a fine example of the service sector acting as a fillip to the growth of the manufacturing sector